Remember the Hoarding: A Public Art Non Happening. (1st June 2017) - Coombs, Gretchen
In June 2015, the Banff Research in Culture's residents contemplated their involvement in a participatory and socially engaged art project in Banff Centre. This article considers this discussion in light of recent contemporary art practices in the public realm, and briefly highlights some of the main theoretical debates circulating at this time.